2019
DOI: 10.1037/abn0000454
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis on the relationship between interoceptive awareness and alexithymia: Distinguishing interoceptive accuracy and sensibility.

Abstract: Alexithymia is a multi-faceted construct consisting of: a) difficulties identifying and describing one's emotions, b) difficulty distinguishing emotional feelings from bodily sensations, c) an "externally-oriented thinking style" focused on external realities with limited self-reflective thought towards inner experience, and d) limited imagination and fantasy life (Nemiah et al., 1976).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 55 publications
6
72
1
Order By: Relevance
“…The subscale has previously been used in interoception research, including in autistic populations, but has not previously been used in people with AN (8,31). A recent metaanalysis found that the BPQ was significantly positively associated with alexithymia (43).…”
Section: Interoceptive Sensibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The subscale has previously been used in interoception research, including in autistic populations, but has not previously been used in people with AN (8,31). A recent metaanalysis found that the BPQ was significantly positively associated with alexithymia (43).…”
Section: Interoceptive Sensibilitymentioning
confidence: 99%
“…Alexithymia is associated with lower interoceptive accuracy, to the extent that it has been hypothesised to be the product of impaired interoception (21,41,42). Furthermore, this relationship may be specific to clinical populations: a recent meta-analysis found no relationship between interoception in control populations, but found that lowered interoception was related to heightened alexithymia in EDs and autism (43). However, this study used a broad definition of interoception, described as "interoceptive awareness," including attention, detection, magnitude, discrimination, accuracy, insight, sensibility, and selfreport abilities surrounding bodily cues (7).…”
Section: Introductionmentioning
confidence: 99%
“…Both ASD and alexithymia are independently associated with heightened anxiety [Berthoz, Consoli, Perez‐Diaz, & Jouvent, 1999; Mandell, 2008] and poorer self‐reported interoceptive sensibility or attention) [DuBois et al, 2016; Mul, Stagg, Herbelin, & Aspell, 2018; Quattrocki & Friston, 2014; Trevisan et al, 2019]. While there are likely multiple reasons for heightened anxiety in ASD associated with core symptom domains (e.g., anxiety from social situations, or anxiety resulting from changes in routines and plans), poor awareness of one's emotions in both ASD and alexithymia would make it difficult to regulate negative emotions and remediate life problems or situations that contribute to anxiety [Swart, Kortekaas, & Aleman, 2009].…”
Section: Our Central Argumentmentioning
confidence: 99%
“…Dysfunctional interoception is theorized to be a relevant mechanism contributing to certain features of autism spectrum disorder [ASD; DuBois, Ameis, Lai, Casanova, & Desarkar, 2016; Quattrocki & Friston, 2014] and alexithymia (i.e., difficulties identifying and describing one's emotions) [Shah, Hall, Catmur, & Bird, 2016; Trevisan et al, 2019], a condition that frequently occurs with ASD [Griffin, Lombardo, & Auyeung, 2016; Hill, Berthoz, & Frith, 2004]. For example, since interoception is hypothesized as being necessary for constructing representations of the “self,” a failure to do so would be expected to (a) inhibit a child's ability to develop skills necessary for self‐reflection, emotional awareness, and homeostatic regulation, and (b) disrupt assimilation of interoceptive and “exteroceptive cues” (i.e., perception of the external world) necessary for observational learning and social communication [Noel, Lytle, Cascio, & Wallace, 2018; Quattrocki & Friston, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…This style of bodily awareness is apparently maladaptive and has traditionally been assessed, due to lack of better instruments, by having patients check a list of anxiety-related symptoms (Porges, 1993). Possibly in part due to the prominence of its author and his polyvagal theory among body-oriented psychotherapists, and despite that fact that his highly popular theory has been seriously questioned, if not thoroughly debunked (Grossman, 2016;Grossman & Deuring, 2020), Porges's questionnaire is still applied in bodily awareness and interoception-related research and has led to considerable confusion in the literature (Mehling, 2016;Trevisan et al, 2019). However, the evenhanded (Williams, 2010), adaptive (salutogenic) style of attention toward bodily sensations, generally labeled "mindful," which is the hallmark of the increasingly popular approaches discussed in this special issue of Kinesiology Review, is clearly not captured by this legacy measure and required the development of new instruments (see the systematic review in Mehling et al, 2009).…”
mentioning
confidence: 99%